Index of periodical literature for the study of the New Testament - Mills, Watson E. (New Testament tools and studies, 2004)
This volume includes more than 15,000 citations to periodical literature published during the twentieth century. Citations are included for each of the books and of the New Testament and these are aranged in canonical order. The specific references are set forth within each canonical book by textual unit. The arrangement of these textual units is the longer before the shorter. There are approximately 175 periodicals included. While the major emphasis is upon English language journals, there are several different language groups represented. The journals included are representative of various theological perspectives. The work includes a comprehensive author index. Index to Periodical Literature for the Study of the New Testament has been selected by Choice as Outstanding Academic Title (2005).